Malnutrition Prevalence and Its Implications on Surgical and Oncological Outcomes in Advanced Ovarian Cancer Patients: A Comprehensive Analysis - Kittithach Pischart; Khemanat Khemworapong; Pattama Chaopotong; Vuthinun Achariyapota (Obstetrics and Gynecology International)
Conclusion: Malnutrition is common among patients with advanced ovarian cancer and is associated with a lower rate of optimal surgery, longer hospital stays, and reduced overall survival rates.